The Antecedents And Outcomes Of Business Units’ Slack: A Prospect Theory Aproach - Fuad, Fuad (2010)

(untitled)
Organizational slack has long been used to explain diverse organizational phenomena and has been regarded as one of building blocks of the behavioral theory of the firm. It has been widely accepted that a comprehensive study to observe the determinants of slack and its performance outcome is the solution for the unsolved puzzles for slack creation. However, prior researches have indeed revealed that the determinants of slack creation itself are yet still inconclusive and the results were ambiguous. The inconclusive and mixed research on the determinants of slack has been normatively prescribed due to lack vigorous, robust model and adopted the piecemeal approach to the measurements of slack creation.